Designing an MVC Model for Rapid Web Application Development - Pop, Dragos-Paul; Altar, Adam (Procedia engineering, 2014)
In this paper, we present a model for rapid web application development. This model is based on the Model-View-Controller architecture (MVC) and has several other useful components like security, form generation and validation, database access and routing. This model was implemented using the PHP programming language, but it can be implemented in other development languages and environments using the same concepts. Improvements in both development and maintenance time have been the main objectives of this research, with the added benefit of correct and maintainable code.